Lactate Clearance: Predictor for Mortality and Therapeutic Response on Severe Sepsis Patient - Siregar, Edwin Saleh; Purnama, Andriana; Rudiman, Reno (BALI MEDICAL JOURNAL; Vol 5 No 2 (2016), 2016)
Background: Severe sepsis and septic shock are at high mortality rate. This high mortality persists as  important aspect in the term of patient treatment which take account in determining aggressiveness of  relevant therapy . Lactate level consideration was considered important among patient under shock,  septicemia, post-operative, acute lung injury, and critical condition. Lactate concentration in static  blood was widely studied and suggested as prognostic value among severe sepsis and septic shock  patient due to the nature of lactate as the result of anaerobic metabolism . Several study documented  the use of lactate as prognostic indicator for shock condition. The increase of lactate concentration  could be useful as the indicator of inadequate oxygen delivery and the existence of anaerobic  metabolism. Lactate clearance investigation is more superior therapeutic target compared with others  oxygen derivate variables.  Methods: This research is a cohort observational study involving  secondary data which was collected from laboratory examination results of study subjects. The  research held from August 2015 to December 2015 in Digestive Division, Surgery Department, Hasan  Sadikin Hospital. 42 patient involved in this study. Results: Comparative test results revealed  significant lactate clearance based on mortality in LCH (6) (p = 0.000) and H (24) (p =0.000) as well.  The level of LC H (6) and H (24) seemed lower in died patient compared with life patient.  Conclusion: This study concluded that lactate clearance in died patient was lower in comparison with  life patient.
Keywords: sepsis, lactate clearance, mortality